Seroconversion of raccoons following two oral rabies vaccination baiting strategies. Issue 1 (29th September 2017) - Berentsen, Are R.; Patrick, Erin M.; Blass, Chad; Wehner, Keith; Dunlap, Brett; Hicks, Bradley; Hale, Robert; Chipman, Richard B.; Vercauteren, Kurt C.
ABSTRACT: Seroprevalence of rabies virus neutralizing antibodies (rVNA) in raccoons ( Procyon lotor ) following oral rabies vaccination (ORV) with RABORAL V‐RG ® in the United States has annually averaged 30% since 1997, a level that is unlikely to successfully interrupt rabies transmission in raccoon populations. A longitudinal ORV zone is maintained in the eastern United States with raccoon variant rabies established east of the zone but absent to the west. However, questions remain regarding the effect of the bait application strategy towards achieving optimal population immunity. We estimated the number of ORV baits/km 2 of raccoon home range and calculated rVNA seroprevalence following 2 ORV baiting strategies: cluster baiting (≤10 baits dropped at a time) via helicopter and hand distribution of individual baits at regular intervals along roads and trails in suburban Chattanooga, Tennessee, USA, during fall 2013 and 2014. We applied baits at 75 baits/km 2 under both strategies. We established 6 1‐km 2 cells in each treatment area, and fitted ≤2 raccoons with global positioning system collars in each cell. We trapped and sampled ≤25 raccoons in each study cell pre‐ and post‐ORV application for rVNA analysis. Overall raccoon home range and core area estimates were 80.7 ha and 17.5 ha, respectively ( n  = 36). Average bait application for home ranges ( n  = 32 home ranges that received bait) was 80.9 baits/km 2 for helicopter baiting and 63.6 baits/km 2 for hand baiting sites. Average bait application for core areas was 104.7 baits/km 2 for helicopter baiting and 69.2 baits/km 2 for hand baiting sites. All home ranges were baited in both treatment areas, whereas 10/18 and 13/14 core areas were baited in the helicopter and hand distribution sites, respectively. Overall, helicopter cluster ORV delivered more baits/km 2 of raccoon home range than hand distribution but was less effective in reaching core areas. Seroprevalence did not change as a function of baiting strategy (helicopter vs. hand baiting). The average overall increase in seroprevalence following ORV application was 8.9%. Evaluation of additional strategies are needed because both methods failed to achieve herd immunity necessary to disrupt rabies transmission in raccoons. © 2017 The Wildlife Society. Abstract : Helicopter cluster bait application and hand baiting by vehicle using Raboral V‐RG have similar results in terms of seroconversion rates and the degree to which the target species has access to bait based on estimated home range. However, evaluation of additional strategies are needed because both methods failed to achieve herd immunity necessary to disrupt rabies transmission in raccoons.